2020
DOI: 10.1101/2020.11.30.20240788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Syphilis self-testing to expand test uptake among men who have sex with men: a theoretically informed mixed methods study in Zimbabwe

Abstract: Objectives: Self-testing for STIs such as HIV and syphilis may empower sexual minorities and expand uptake of STI testing. While much is known about HIV self-testing (HIVST), less is known about syphilis self-testing, particularly in low-income settings. The objective of this study is to determine context-specific facilitators and barriers for self-testing and to assess the usability of syphilis self-testing in Zimbabwe among men who have sex with men (MSM). Methods: This mixed methods study was conducted in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Self-testing involves a person conducting and interpreting their own test result. Clinic closures and travel restrictions during COVID-19 have accelerated syphilis self-testing uptake ( 20 , 21 ) and expanded self-sampling pilots ( 22 ). Expanding these opportunities for syphilis testing in diverse settings could help to catalyze more syphilis control programs, policies, and research.…”
Section: Covid-19 and Syphilismentioning
confidence: 99%
“…Self-testing involves a person conducting and interpreting their own test result. Clinic closures and travel restrictions during COVID-19 have accelerated syphilis self-testing uptake ( 20 , 21 ) and expanded self-sampling pilots ( 22 ). Expanding these opportunities for syphilis testing in diverse settings could help to catalyze more syphilis control programs, policies, and research.…”
Section: Covid-19 and Syphilismentioning
confidence: 99%
“…A study conducted in Zimbabwe to assess the usability of syphilis self-testing in MSM reported high self-test usability and found that self-testing provided increased privacy, convenience and autonomy in comparison to hospital/clinic-based testing. 24 In China, syphilis self-testing increased testing rates amongst MSM who had never tested for syphilis in the hospital (adjusted odds ratio [aOR]: 2.96; 95% confidence interval [CI]: 1.86–4.72). 18 The similarities between HIV self-testing and syphilis testing may increase the acceptability of syphilis self-testing amongst KPs in Zimbabwe because some of the patients may be familiar with HIV self-test kits on the market, for example, the HIV OraQuick.…”
Section: Strategies To Improve Syphilis Testing Rates Amongst Key Pop...mentioning
confidence: 99%
“… 18 The similarities between HIV self-testing and syphilis testing may increase the acceptability of syphilis self-testing amongst KPs in Zimbabwe because some of the patients may be familiar with HIV self-test kits on the market, for example, the HIV OraQuick. 24 It is important, however, to ensure the availability of facility-based confirmatory testing for patients who have reactive screening tests. To successfully implement this approach, there is a need to craft guidelines and education material specific for KPs on the correct use of devices and consider any concerns that might be barriers to the implementation of syphilis self-testing.…”
Section: Strategies To Improve Syphilis Testing Rates Amongst Key Pop...mentioning
confidence: 99%